Role of Zinc in Low Birth Weight Neonates - Hoque, Aminul; Ali, Shah Md Keramat (Bangladesh Medical Journal, 2009)
Background: Evidence for an effect of zinc supplementation on growth in every young infants in developing countries is scarce and inconsistent. In Bangladesh, the highest incidence of Low Birth Weight (LBW) is the main cause of neonatal mortality and morbidity. It is hypothesized that LBW neonates is zinc deficient and that might adversely affect postnatal growth. The present study was carried out to measure the effect of zinc supplementation on LBW neonates during the first month of life and to observe the growth pattern of supplemented (zn) with non supplemented group. Aim and Objective: It is supported by literates that zinc has an effective positive role in the growth and development in children. But evaluation of the effect of zinc on weight gain in LBW not done so our primary objectives are. (1) The study was done to measure the effectiveness of zinc supplementation on weight gain in low birth weight neonates. (2) To list low birth weight (LBW) babies admitted in neonatal ward of Pediatrics Department of Sher-E-Bangla Medical College Hospital, Barisal during one clander year. (3) To supplement Zinc in a group low birth weight neonate and to compare with another group of low birth weight neonate will receive placebo for a period of 28 days along with necessary treatment for both groups. (4) To compare the study group with control to find out where and when zinc have contributed to weight gain, side effect of supplementation and acceptance of supplementation by the neonates. Materials and methods : In a randomized, double-blind, placebo-controlled trial study of the effect of zinc on weight gain in low birth weight neonates. The study was carried out in the neonatal ward of pediatrics department of Sher-E-Bangla Medical College, Barisal, Bangladesh. The duration of the study was from May '05 to May '07. The research proposal was approved by Faculty of Post-graduate Medical Science and Research, Dhaka University. Ethical clearance was obtained from Bangladesh Medical Research Council (BMRC). One hundred low birth weight neonates were included in this study and the same number of controls matched for birth weight sex, types to LBW, feeding pattern was studied. After randomization and pair matched neonates were grouped into two groups, 100 neonates were included in group A and 100 neonates in group B. In the first 28 days of life, the A group received Syrup D1 2.5ml/day in and B group received syrup D2 2.5ml/day. The syrup administered to the study neonate in two groups were prepared by Orion Laboratories Ltd. drug manufacturing company. Syrup D1 2.5ml contains zinc 5mg was given to A group and Placebo (D2) for B group. The two syrups were indistinguishable in taste and color and code of syrup 'D1' and 'D2' was kept strictly confidential with the pharmacist. The parents or care giver were instructed to feed syrup D1 2.5ml or syrup D2 every morning at 10 am to their neonate up to 28 days. Measurement of weight of case and control without cloth before feeding at 9a.m after 3 days, 7 days, 14 days, 21 days and 28 days and recorded in a record form. The overall supervision was maintained by researcher. At the end of the study the code of syrup was decoded and found 'D2' for Placebo and D1> for zinc. Data were analyzed by using statistical software SPSS. Result : Among the study subjects 54% of them were male and 46% were female, of them 78% were preterm, and were 22% IUGR. The mean (±SD) birth weight was 1789.50 ± 228.89gm is for cases and controls. Three days after birth, weight decreases to (1610.50 ± 255.38gms) in cases and to (1613.00 ± 215.04 gms) in controls. More weight gain in cases than controls was observed after 7 days of birth. Highly significant weight gain after 21 days (2261.50 ± 296.14 gms) in cases than controls (2165.50 ± 243.47 gms) and 28 days (2665.00 ± 331.52 gms) in cases observed than controls (2374.00 ± 410.07 gms). So mean weight after 21st and 28th days of cases was significantly higher (P<0.05) than that of control group respectively. Mean weight gain (31.37 ± 6.91 gm/day) of cases was significantly higher (P<0.000) than the mean weight gain (21.63 ± 5.67 gm/day) of control group. Mean weight of final follow up of zinc group was 2665.00 ± 331.52 and placebo group was 2374.00 ± 4107. (P<0.000) when compared with mean birth weight. Linear curve of effectiveness of the program on weight for age z-score by follow up days. It was found that increment of effectiveness in Zinc group was higher than that of placebo group. Eighty four percent of cases gained weight more than control group. Problems like physiological Jaundice, infection, convulsion, were less in zinc group compared to control group. Conclusions : Neonatal mortality in Bangladesh is high as experienced by causes of death during Neonatal period due to low birth weight. The result of the study provide evidence that zinc supplementation in low birth weight enhanced more weight gain and experienced less problems like infection, convulsion and Jaundice. There was no adverse effect in zinc supplementation groups. Therefore, we conclude that zinc supplementation to LBW neonates is beneficial to combat curse of low birth weight. DOI: 10.3329/bmj.v38i1.3583 Bangladesh Medical Journal 38(1) 2009 24-30